CMOS low voltage class AB amplifier - Po, Po. (2008)
Techniques required to design the circuit to work in low voltage were reviewed and presented in this report. The amplifier operates with a 1.5 V power supply voltage. It performs to a 30kHz bandwidth at a 33dB gain, with rail-to-rail input and output, driving a low impedance load of 32 Ohm, with an output stage biased in Class AB.